Urgensi Para Profesi Sebagai Gatekeeper Dalam Tindak Pidana Pencucian Uang - Budi Bahreisy; N. Nurmalawaty; Rini Anggreini; Devi Yulida; Anak Agung Gede Ananta Sahadewa (Fakultas Hukum, Universitas Warmadewa, 2026)
One of the issues that arises in the context of money laundering is the concept of gatekeepers. This concept involves imposing reporting obligations on financial service providers and providers of goods and services. However, for professionals such as lawyers and notaries, these rules have not been accommodated. The problem discussed in this paper is the importance of professional roles as gatekeepers in the realm of money laundering. The research methodology employed in this paper is normative legal research, which refers to legal norms found in legislation and court decisions. The research approach used includes a legislative approach and a conceptual approach. Several points become contentious among professions, hindering the implementation of the gatekeeper concept in Indonesia. Firstly, there are some professions that have yet to fully grasp this concept, despite their potential role as gatekeepers, such as notaries. Secondly, there is a conflict between client confidentiality and the role of a professional, for instance, between clients and lawyers. This creates a dilemma where, on one hand, a lawyer must maintain client confidentiality, but on the other hand, is required to report suspicions. Thirdly, there is resistance from the legislature (DPR) regarding the adoption of this concept, even though the legislature plays a crucial role in shaping laws.